The effect of short-term of fine particles on daily respiratory emergency in cities contaminated with wood smoke - R. Torres; N. Baker; G. Bernal; F. Peres; A. Maldonado; D.D. Caceres (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The goal of this study is to evaluate in a time-series study the short-term effects of particulate matter-2.5exposure on respiratory emergency visits in six central-southern Chilean cities highly contaminated by wood smoke. METHODS: Association was assessed using both distributed lag linear and non-linear Poisson models constrained to a 7-day lag period, adjusting for temporal trends and meteorological variables and stratifying seasonally into cold and warm periods. FINDING: The results showed that the daily average concentrations of particulate matter-2.5in the cold period were 3 to 6 times those recorded in the warm period, exceeding the daily norm of 50 µg/m3 the 93.3% of the time versus 6.7%, respectively. The average daily number of respiratory emergency visits were between 30% and 64% higher in the cold period compared to the warm one. From linear models, cumulative relative risk ratios over 0-7 day lags per 10 mg/m3 of fine particle increase were between 1.004 (95% confidence Interval: 0.998 - 1.010) and 1.061 (95% confidence Interval: 1.049 - 1.074); these annual effects are attributable to the cold period impact where the cumulative risk ratios  were between 1.008 (95% confidence Interval: 1.004 - 1.012) and 1.036 (95% confidence Interval: 1.026 - 1.047), since significant effects of fine particles on the studied risk were not found for the warm period. CONCLUSION: With non-linear models we observed strong increasing associations with the level of particles for the overall period. High levels of fineparticles from firewood are associated with respiratory effects observable several days after exposure. Health effects found in this study suggest that current policies tending to mitigate woodsmoke-related emissions should continue and reinforce.